Regulating cation disorder to stabilize oxygen redox in Li-rich DRX cathodes via Fe substitution - Chia-Ching Lin; Péter Udvarhelyi; Hao-Hsiang Chang; Tsung-Yi Chen; Zhenfei Cai; Yu Zhao; Han-Yi Chen; Denis Y.W. Yu (Chemical Engineering Journal, 2026)

Amorphous CO2-philic molecular networks via covalent coupling for high-performance TFC hollow fiber membranes - Meta Mamo Goro; Zelalem Gudeta Abdi; Qing-Yun Chou; Ching-Han Chou; Che-Wei Chang; Tai-Shung Chung (Chemical Engineering Journal, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Use of AI-mediated image analysis to investigate the influence of environmental factors and recreational scuba diving on fish activity patterns in a marine protected area - Ching-Han Chang; Dong-Lin Li; Li-Shu Chen; Yi-Ta Shao (Regional Studies in Marine Science, 2026)

Phylogeny and Taxonomy of the Coral Reef Maidenhair Fern Adiantum capillus‐veneris subsp. lanyuanum (Pteridaceae) in East Asia - Zhi‐Xiang Chang; Tian‐Chuan Hsu; Xinping Qi; Ching Ming Hsieh; Atsushi Ebihara; Yi‐Han Chang; Yao‐Moan Huang; Li‐Yaung Kuo (New Zealand Journal of Botany, 2026)
Adiantum capillus‐veneris is a species with a worldwide distribution, exhibiting considerable morphological variation, with several infraspecific names applied. Among these infraspecific taxa, A. capillus‐veneris subspecies lanyuanum can be easily distinguished from typical A. capillus‐veneris by its small and 1‐pinnate fronds. This form has been recorded from a few insular populations in Taiwan and Japan, typically inhabiting moist and shaded coral reef cliffs. A chloroplast DNA phylogeny further demonstrates that collections of subsp. lanyuanum across different populations formed a well‐supported clade, and also provides evidence of its genetic distinctiveness and differentiation. Further examination of herbarium specimens and field observations found that, in addition to frond morphology, the rhizome scale differences are also useful for distinguishing the two taxa. As a consequence, A. capillus‐veneris subsp. lanyuanum comb. nov. is proposed as the appropriate taxonomic designation of this taxa and a neotype is designated.

Development of a pomelo pectin–based microencapsulation system for Akkermansia muciniphila - Chang-Han Wang; Wen-Yu Liu; She-Ching Wu (Food Chemistry, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Development of a high-sensitivity dopamine sensor using copper tungstate nanoparticle-decorated carbon nanofibers on a glassy carbon electrode for analysis in various biological samples - Kiruthika Mariappan; Jing-Han Teng; Fu-Yi Chang; Shen Ming Chen; Jenn Fang Su; Ching-Lung Chen (Journal of Environmental Chemical Engineering, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

Empagliflozin attenuates sorafenib-promoted renal ferroptosis and inflammation by targeting cyclooxygenase-2/prostaglandin E2 axis - Ming-Kai Tsai; Wen-Chin Lee; Shih-Chung Huang; Chao-Cheng Huang; Yi-Chen Wang; Chien-Han Yuan; Chih-Chiang Wang; Ching-Han Liu; Nan-Chieh Huang; Yi-Chen Chang; Cheng-Chieh Fang; Bi-Wen Yeh; et al. (Toxicology and Applied Pharmacology, 2025)

Plasma-guided green synthesis of crystalline graphene quantum dots for broad-spectrum antiviral applications - Ren-Jie Weng; Li-Syuan Wu; Darwin Kurniawan; Ching-Tzu Chang; Ming-Han Tsai; Wei-Hung Chiang (Chemical Engineering Journal, 2025)

A neutral multivalent AIE–TICT scaffold: An off-on, wash-free fluorogenic strategy for biosensing glycan–protein interactions in live cells and mycobacteria - Huai-En Chang; Chien-Chin Chen; Yi-Jin You; Pei-Hsuan Lee; Bo-Chang Ruan; Hong-Luen Kwok; Ching-Tse Wu; Chuang-Rung Chang; Jiun-Han Chen; Eugene C. Lin; Pei-Jhen Li (Analytica Chimica Acta, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

Comprehensive validation of a compact laser speckle contrast imaging system for vascular function assessment: from the laboratory to the clinic - Meng-Che Hsieh; Chia-Yu Chang; Ching-Han Hsu; Congo Tak Shing Ching; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Possible role of autophagy in microbial volatile pollutant-induced starch degradation and expression of hypoxia responsive genes - Chung-Chih Huang; Ching-Han Chang; Tu-Trinh Thi Truong; Wu-Guei Wang; Che-Hui Lin; Chih-Yun Chiang; Iwai Obayashi; Hao-Jen Huang (Environmental Pollution, 2025)

The difference in roaming behavior between owned and unowned dogs in a satoyama landscape area - Tsung-Han Kuo; Gau-Ming Chang; Pin-Huan Yu; Wei-Hsuan Chen; Shih-Ching Yen (Applied Animal Behaviour Science, 2025)

Piezocatalytic property of PVDF/Graphene self-assembling piezoelectric membrane for environmental remediation - Tsung-Han Huang; Franz Kenneth C. Espino; Xin-Yuan Tian; Januar Widakdo; Hannah Faye M. Austria; Owen Setiawan; Wei-Song Hung; Kristopher Ray S. Pamintuan; Rhoda B. Leron; Ching-Yuan Chang; Alvin R. Caparanga; Kueir-Rarn Lee; et al. (Chemical Engineering Journal, 2024)

Velocity distribution and movement of multiple slow-moving landslides characterized by an optimized MTInSAR workflow - Chiao-Yin Lu; Yu-Chang Chan; Jyr-Ching Hu; Chun-Ying Chiu; Chung-Ray Chu; Chia-Han Tseng; Chih-Hsin Chang (Engineering Geology, 2023)

Uncovering molecular mechanisms involved in microbial volatile compounds-induced stomatal closure in Arabidopsis thaliana - Tu-Trinh Thi Truong; Chi-Chou Chiu; Jing-Yu Chen; Pei-Yu Su; Tri-Phuong Nguyen; Ngoc-Nam Trinh; Tetsuro Mimura; Ruey-Hua Lee; Ching-Han Chang; Hao-Jen Huang (Plant Molecular Biology, 2023)

The involvement of AtMKK1 and AtMKK3 in plant-deleterious microbial volatile compounds-induced defense responses - Ching-Han Chang; Wu-Guei Wang; Pei-Yu Su; Yu-Shuo Chen; Tri-Phuong Nguyen; Jian Xu; Masaru Ohme-Takagi; Tetsuro Mimura; Ping-Fu Hou; Hao-Jen Huang (Plant Molecular Biology, 2023)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

A panel analysis of the Mahjong card game and social activity with sleep-related measurements among Chinese older adults - Yen-Han Lee; Yen-Chang Chang; Mack Shelley; Ching-Ti Liu (Sleep and Biological Rhythms, 2020)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

Evaluating the associations of consumption of non-red meat protein sources and flavor preferences on sleeping patterns among older adults in China - Yen-Han Lee; Yen-Chang Chang; Ching-Ti Liu; Mack Shelley (Sleep and Biological Rhythms, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Dietary patterns with fresh fruits and vegetables consumption and quality of sleep among older adults in mainland China - Yen-Han Lee; Yen-Chang Chang; Yi-Ting Lee; Mack Shelley; Ching-Ti Liu (Sleep and Biological Rhythms, 2018)

Slip monitoring of a dip-slope and runout simulation by the discrete element method: a case study at the Huafan University campus in northern Taiwan - Chia-Han Tseng; Yu-Chang Chan; Ching-Jiang Jeng; Yu-Chung Hsieh (Natural Hazards, 2017)

Arsenic speciation in rice and risk assessment of inorganic arsenic in Taiwan population - Hsiu-Ling Chen; Ching-Chang Lee; Winn-Jung Huang; Han-Ting Huang; Yi-Chen Wu; Ya-Chen Hsu; Yi-Ting Kao (Environmental Science and Pollution Research, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Differential gene expression in human hepatocyte cell lines exposed to the antiretroviral agent zidovudine - Jia-Long Fang; Tao Han; Qiangen Wu; Frederick A. Beland; Ching-Wei Chang; Lei Guo; James C. Fuscoe (Archives of Toxicology, 2013)

Data-oriented analyses of ciliate foraging behaviors - Yang-Chi Chang; Jang-Ching Yan; Jiang-Shiou Hwang; Cheng-Han Wu; Meng-Tsung Lee (Hydrobiologia, 2011)

Increasing trend of the incidence of esophageal squamous cell carcinoma, but not adenocarcinoma, in Taiwan - Ching-Liang Lu; Hui-Chu Lang; Jiing-Chyuan Luo; Chun-Chu Liu; Han-Chieh Lin; Full-Young Chang; Shou-Dong Lee (Cancer Causes & Control, 2010)

Effects of chronic 4-n-nonylphenol treatment on aortic vasoconstriction and vasorelaxation in rats - Chi-Ying Hsieh; Chang-Ling Miaw; Chien-Cheng Hsieh; Hui-Ching Tseng; Yuan-Han Yang; Chia-Hung Yen (Archives of Toxicology, 2009)

Expression and localization of Tmie in adult rat cochlea - Mao-Chang Su; Jiann-Jou Yang; Ming-Yung Chou; Chung-Han Hsin; Ching-Chyuan Su; Shuan-Yow Li (Histochemistry and Cell Biology, 2008)

Sequencing and Amplified Restriction Fragment Length Polymorphism Analysis of Ribonucleotide Reductase Large Subunit Gene of the White Spot Syndrome Virus in Blue Crab (Callinectes sapidus) from American Coastal Waters - Yun-Shiang Chang; Shao-En Peng; Han-Ching Wang; Hui-Chen Hsu; Ching-Hui Ho; Chung-Hsiung Wang; Sho-Ya Wang; Chu-Fang Lo; Guang-Hsiung Kou (Marine Biotechnology, 2001)